Neurological rehabilitation in post COVID-19 patients. Literature review - Betancourt-Peña, Jhonatan (2023)
Introduction: COVID-19 infection is responsible for a heterogeneous clinical syndrome that can lead to severe pneumonia and acute respiratory distress syndrome. While the primary symptoms of COVID-19 are respiratory in nature, there is evidence of central nervous system disorders that require rehabilitation. Objective: This study aims to describe neurological disorders, their evaluation, and key aspects of clinical management in patients with COVID-19, based on a review of available evidence. Methods: We conducted a literature review by searching various databases, including MEDLINE, PEDRO, PubMed, SpringerLink, Ovid, Scielo, and Google Scholar. Results: The main disorders observed in post-COVID-19 patients include: loss of smell and taste, encephalopathy, Guillain-Barré Syndrome, headaches, and other cerebrovascular complications. In terms of evaluation, it is essential to assess the patient's medical history, functionality, aerobic capacity, anxiety, depression, quality of life, and conduct a comprehensive neurological examination covering sensitivity, gait, balance, muscle tone, cognition, and level of consciousness. Recommended intervention strategies encompass aerobic training, neuromuscular facilitation, electrostimulation, education, and proper positioning. Conclusion: Neurological rehabilitation for post-COVID-19 patients with neurological disorders helps prevent physical deconditioning and the complications associated with prolonged immobilization. Furthermore, it facilitates the restoration of motor function, enhances cognitive and emotional well-being, ultimately reducing disability, restoring independence, and improving overall quality of life.